An Analysis of Tevfik Fikret's 'Sis' and Abdülbaki Fevzi's "Sis'e Nazire" - Ünlü, Bedirhan (Mardin Artuklu University, 2025)
“Sis” is one of the most influential poems in Turkish literature, having inspired numerous literary responses both at the time of its publication and in subsequent years. In this poem, Tevfik Fikret articulates his reproach and disillusionment with Istanbul in an uncommonly harsh tone, marking a stylistic innovation in Turkish poetry. This novel approach continued to influence poets well into the Republican era. Since Yahya Kemal, many poets have positioned themselves either in opposition to or in support of "Sis". What makes "Sis’e Nazire" noteworthy is its intermediate stance between these opposing views. This poem, published in two parts under the titles "Sis’e Nazire" and "Sis Naziresinin Mabadı" in the newspaper Zümrüd ü Anka, was penned by Abdülbaki Fevzi, a relatively obscure figure in Turkish literary history who contributed humorous poems to various newspapers and journals. Some of these works parody well-known poems in Turkish literature and can be classified within the "hezl" tradition of classical Ottoman poetry. Among these parodied works are poems by Yahya Kemal and Ahmet Haşim. In accordance with the characteristics of the hezl genre, "Sis’e Nazire" humorously reinterprets Fikret’s "Sis". While Tevfik Fikret reflects a mood of existential anguish, Abdülbaki Fevzi shifts the focus to the material struggles of poverty and destitution. The main theme of Fevzi’s work is the impact of financial hardship on the poet. Despite its humorous tone, the poem retains the formal elements of Sis, including rhyme scheme, aruz meter, and verse form. The primary distinction of "Sis’e Nazire" lies in its style and metaphorical usage; while adhering to the external structure of "Sis", it diverges significantly in content. Abdülbaki Fevzi humorously reinterprets Fikret’s original metaphors, and in some instances, introduces his own unique metaphorical expressions. This study compares Tevfik Fikret’s "Sis" and Abdülbaki Fevzi’s "Sis’e Nazire" in terms of content, structural elements, style, and metaphorical usage.

"Sis", yazıldığı yıllarda ve sonrasında üzerinde çokça edebî etkilenmenin yaşandığı manzumelerden biridir. Tevfik Fikret, "Sis"te İstanbul'a dair sitem ve serzenişlerini o döneme kadar rastlanılmayan sert bir üslupla dile getirir. Türk şiirinde yeni olan bu söylem, etkisini Cumhuriyet Dönemi'ne kadar sürdürür. Yahya Kemal'den itibaren pek çok şair "Sis"in karşısında veya yanında konumlanmıştır denilebilir. "Sis'e Nazire" manzumesi ise bu iki karşıt durum arasında yer almasıyla öne çıkar. Manzume, "Sis'e Nazire" ve "Sis Naziresinin Mabadı" başlıklarıyla Abdülbaki Fevzi tarafından Zümrüd ü Anka gazetesinde iki kısım hâlinde yayımlanır. Türk edebiyatı tarihinde ismi geri planda kalmış olan Abdülbaki Fevzi, çeşitli gazete ve dergilerde manzumeler kaleme alır. Bu manzumelerin bir kısmı, Türk edebiyatında meşhur olan şiirlerin mizahi bir üslupla yeniden yorumlanmasından oluşur. Divan şiirinin hezl türü içerisinde değerlendirilebilecek olan bu eserler arasında Yahya Kemal ve Ahmet Haşim'in bazı manzumeleri de bulur. Abdülbaki Fevzi'nin "Sis'e Nazire" başlıklı şiiri hezl türünün özelliğine uygun olarak "Sis"i mizahi bir üslupla yorumladığı manzumesidir. Tevfik Fikret'in bunaltılı ruh hâli, Abdülbaki Fevzi'nin kaleminde maddi sıkıntılar düzlemine kaydırılır. Parasızlık ve sefaletin şair üzerinde bıraktığı etki manzumenin ana konusudur. Eser boyunca mizahi üslubu bırakmayan şair, "Sis"in dış yapı özelliklerini terk etmez. Uyak şekli, aruz ölçüsü ve nazım şekli aynen devam ettirilir. "Sis"le içerik olarak farklı, dış yapı unsurları itibarıyla aynı olan "Sis'e Nazire"nin öne çıkan özelliği ise üslup ve metaforik kullanımlarda görülür. Tevfik Fikret'in yakaladığı özgün metaforik kullanımlar Abdülbaki Fevzi tarafından mizahi bir üslupla ele alınır. Abdülbaki Fevzi'nin metaforik kullanımlarının yer yer özgün bir şekilde ortaya çıkması dikkat çekicidir. Yapılan bu çalışmada Tevfik Fikret'in "Sis" manzumesiyle Abdülbaki Fevzi'nin "Sis'e Nazire" başlıklı şiirleri içerik, yapı unsurları, üslup ve metaforik kullanımlar açsından karşılaştırmaya tabi tutulmuştur.
Tevfik Fikret'in "Sis" ve Abdülbaki Fevzi'nin "Sis'e Nazire" Adlı Şiirleri Üzerine Bir İnceleme
Keywords: Literary Theory; Edebi Teori